Perceptions of community members on contextual factors driving cardiovascular disease behavioural risk in Ghana: a qualitative study - Naa Adjeley Mensah; Olutobi Adekunle Sanuade; Leonard Baatiema (BMC, 2022)
Abstract Background There is clear evidence that lifestyle interventions are effective towards reducing cardiovascular risk. However, implementing these interventions in real-world setting has been suboptimal, especially in sub-Saharan Africa, thus creating 'evidence to practice gap.' We explore perceptions of community members on contextual factors driving cardiovascular disease (CVD) behavioural risk (alcohol consumption, smoking, physical (in)activity and fruits and vegetables consumption) in Ghana. Methods This was a cross-sectional study. Thirty (30) focus group discussions (FGDs) were carried out in five communities in Ghana (Ga Mashie, Tafo, Gyegyeano, Chanshegu and Agorve) between October and November 2017, and these were analysed using a thematic approach. Results Five main factors were raised by participants as contextual factors driving alcohol consumption and smoking and these include economic (poverty, unemployment, loss of jobs), psycho-social (worries, hardships, anxieties), medical (pain suppression, illness management), sexual (sexual performance boost), and socio-cultural (curse invocation, quest for supernatural powers) factors. Personal/social factors (time constraints, personal dislike, lack of knowledge of the benefits of exercise), economic factors (poverty, economic hardship), and negative health effects (getting tired easily, medical conditions) were cited as reasons why community members did not engage in physical activity. Consumption of fruits and vegetables in the five communities were determined by availability, cost, personal (dis)like, lack of knowledge about benefits, and cultural taboo. Participants' narratives revealed that the symbolic functions of some of these behavioural risk factors and the built environment were important determining factors that have sustained these behaviours in these communities over the years. Conclusions This study showed that successful implementation of CVD interventions in Ghana needs to address the perceptions of community members on factors driving CVD behavioural risk factors. Future policies and interventions should be developed based on these contextual factors taking into consideration the age, sex and ethnic variations especially with interventions seeking to address CVD risk factors at the primary health care level. These findings should urge local policy makers and health managers to incorporate the roles of these contextual factors in new programs targeting cardiovascular health. Closing the 'evidence to practice' gap as far as CVD interventions are concerned may be impossible without this.